PEMBERDAYAAN KAUM DHUAFA SEBAGAI IMPLEMENTASI DAKWAH SOSIAL MAHASISWA - Siti Nurkholifah; Siska Ariyanti; Ghania Azzahra (CV. ADIBA AISHA AMIRA, 2026)
Poverty is a social problem still faced by society, especially the underprivileged who live with limited economic and health resources. This empowerment activity was carried out by students of the Economics Education Study Program at Muhammadiyah University Prof. Dr. Hamka as a form of social preaching and community service. This program focused on providing basic necessities assistance to underprivileged families based on field observations. The implementation method was carried out through fundraising, aid distribution, and activity evaluation. The results of the activity showed that the assistance provided was able to ease the economic burden of beneficiaries and foster social awareness among students. This activity is expected to become a means of social learning and the implementation of Islamic values ​​in community life